PERAN PUSAT KEGIATAN BELAJAR MASYARAKAT SEBAGAI LEMBAGA PEMBERDAYAAN NARAPIDANADI LAPAS KLAS IIB MERAUKE - Zein, Syahmuhar M. (JURNAL EKOLOGI BIROKRASI, 2015)
Center for Social Studies Activities which is known as PKBM, Indonesian abbreviated for Pusat Kegiatan Belajar Masyarakat (Center for Social Studies Activities) has the relevant meaning with the Social Empowering System regulated in 12th Constitution 1995 about The Socialization (UU Nomor 12 Tahun 1995 tentang Pemasyarakatan). This constitution gives a new perspective perception in Indonesian Laws Enforcement to totally change from the old system of punishment which was no civil and human right considerations to totally civil and human right considerations. In accordance with this tremendous challenge PKBM as one among some of social empowering, education, training, and development units within The Socialize Foundation of 2nd Class Merauke, Ministry of Laws and Human Right Republic of Indonesia. To see that resources linkage within the PKBM which was built since 2009 until now there are many problems connected with human resources management to manage the PKBM foundation. All ideas and programs are still directly controlled and executed by the principle alone. No team work under a system, no experience in social-organization to exist, limit superstructures and facilities make stagnancy in the PKBMâs training and education activities. No well coordination yet as no commitment of training & development, education and empowering programs processing between the The Socialize Foundation of 2nd Class Merauke, Ministry of Laws and Human Right Republic of Indonesia and the PKBM. No operational costs and annual planning and budgeting from the Socialize Foundation (Lapas) planned for PKBM. The Socialize Foundation must take advantages with the existence of PKBM as a unit of office work who can assist the commitment of training & development, education and empowering programs in the The Socialize Foundation of 2nd Class Merauke, Ministry of Laws and Human Right Republic of Indonesia. If the Socialize Foundation (Lapas) has already understood the functions of the PKBM in assisting empowering activities such as vocational training & education and also PKBM is able to open some access for getting fund or financial from central government ministries even open the social donation from companies or industries to fulfill needs of empowering human resources training & development in The Socialize Foundation of 2nd Class Merauke. We hope the good will between the two foundations will allocate the annual socialize empowering fund to help operational cost of programs. As the conclusion of problems within the Tunas Mandiri PKBM I divide cases into two road map. They are the coordination problem with the principle or manager of The Socialize Foundation of 2nd Class Merauke and the un-capable PKBM administration staff to execute their jobs descriptions professionally, in high motivations, creativities and dedications. If this two cases can be solved properly then Tunas Mandiri PKBM will be a good pilot project foundation for the nation-wide Socialize Foundation in the Ministry of Laws and Human Right Republic of Indonesia. Keywords : Socialize Foundation, Ministry Of Law And Human